Ethno-communal crisis and its implication on food security and business activities in Nigeria - Felix E. Ojong; A. M. Ogaboh Agba; Chinenye J. Njirinze; Pius U. Angioha (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
This assessed available information on the effect of ethno-communal crisis on food security and business activities in Nigeria. Literature was reviewed according to the variables raised in the study. The study adopted Eco-violence theory for the study. The survey design was used in the study. Four hundred (400) participants from Yakurr Local Government Area of Cross River State were selected using purposive and simple random sampling techniques. Data was gathered from respondents using a structured questionnaire. Results revealed that ethno-communal crisis has a significant impact on food security and business activities. It was recommended that the government, in collaboration with traditional rulers, should set up well-defined boundaries between communities.